1999
DOI: 10.1046/j.1365-2710.1999.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Programme to improve the use of drugs in older people and involve general practitioners in community education

Abstract: As part of a multi-pronged approach to improving the quality of drug use in the elderly, a pharmacist was contracted by the Division of General Practice (Northern Tasmania) to develop educational material and implement two academic detailing sessions for general practitioners on the issues of adverse drug reactions and drug interactions in older people. The project aimed to involve general practitioners in community education after optimizing relevant therapeutic knowledge and standardizing prescribing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…For >20 years, specialist clinical pharmacists have worked with general practices, GPs, and practice nurses to achieve improvements in patient care via clinical medication review and prescribing cost-efficiencies across the UK, North America, and Australasia. [7][8][9][10]12,13,15,16 Maintaining these gains, and delivering nWOW and expanded pharmacist services, will be a challenge against a background of medicines shortages, large and sharp increases in drug prices, and funding constraints. [27][28][29] As with other professions, challenges exist in recruiting pharmacists to general practices in rural areas.…”
Section: Implications For Research and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…For >20 years, specialist clinical pharmacists have worked with general practices, GPs, and practice nurses to achieve improvements in patient care via clinical medication review and prescribing cost-efficiencies across the UK, North America, and Australasia. [7][8][9][10]12,13,15,16 Maintaining these gains, and delivering nWOW and expanded pharmacist services, will be a challenge against a background of medicines shortages, large and sharp increases in drug prices, and funding constraints. [27][28][29] As with other professions, challenges exist in recruiting pharmacists to general practices in rural areas.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…14 Similar initiatives have evolved in North America and Australia. 8,15,16 In the main, UK prescribing teams predominantly consist of specialist clinical pharmacists and pharmacy technicians; however, there are large variations in where, how, and what services are provided. In part, this is due to differences in funding models, local and national agendas, and pressures on current systems and services.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the proportion of older patients using at least one psychoactive agent was reduced to 65 % after the education phase compared to 80 % before the project [18]. Similarly, CE on appropriate geriatric prescribing appears to improve pharmacists' performance in older people care.…”
Section: Main Textmentioning
confidence: 99%
“…One randomized controlled trial infers that pharmacists with specialized training could reduce medical costs, 35 whereas three randomized controlled trials found that pharmacist-led medication review led to negligible changes in costs. Further difficulties are created by the lack of competent economic analyses on the value and contribution of pharmacy-led medication review to the medication management of older people.…”
Section: Outcomes Of Pharmacist-led Medication-review Researchmentioning
confidence: 99%